Analisa Pengaruh Transparansi, Kredibilitas, Pengetahuan, Religiusitas terhadap Motivasi Membayar Zakat dengan Teknologi Digital sebagai Variabel Moderating di LAZ Nurul Hayat Medan - Munawar, Rahmat; J. Nst, Yenni Samri; Ridwan, Muhammad (el Buhuth: Borneo Journal of Islamic Studies, 2022)
The motivation to pay zakat is to be willing to pay zakat by demanding incentives to pay it. Zakat is an obligation for Muslims to eradicate poverty and poverty in society and the ummah. The purpose of this study was to determine the effect of the variables of transparency, trust, knowledge, and religiosity on the motivation to pay zakat and the effect of the moderating variable of digital technology, as well as to determine the effect of the variables of transparency, trustworthiness, knowledge, and religiosity on motivation for the moderating variable of digital technology. on Zakat Payments at LAZ Nurul Hayat Medan. Significant effect on credibility, knowledge, religiosity, and motivation to pay zakat, up to 76.2%. Transparency, trustworthiness, knowledge, religiosity, and the level of moderation of digital technology have a huge impact on motivation to pay zakat up to 85.5%. The results of the significance test show that the variables of transparency, trust, knowledge, and religiosity have a significant and significant effect on the motivation to pay zakat. The moderating variable of digital technology can moderate religiosity about the motivation to pay zakat, but the moderating variable of digital technology is not able to moderate transparency, credibility, knowledge on motivation to pay zakat at LAZ Nurul Hayat Medan